Isolation and Screening of Bacteria with Antibiotic-producing Properties From the Soil at the Marmara and New Market Abattoirs, Wukari (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Antimicrobials are substances made by organisms that harm other organisms. Rising antibiotic resistance is a global issue, creating a need for alternative treatments. This study screened bacteria with antimicrobial properties from Marmara and New Market abattoirs in Wukari, Nigeria. Twelve soil samples were collected at each location from four sites: slaughtering, animal waste dumping, washing, and point of sale. Samples were taken at three soil depths: 0 cm, 10 cm, and 30 cm, totaling 24 samples. Isolates were screened and preliminarily identified using conventional methods. Eleven (11) bacterial species were isolated, which are Enterobacter species (N1, N2, N3), Pseudomonas species (N4), Staphylococcus epidermidis (N5), Escherichia coli (N6), Staphylococcus aureus (N7), Salmonella species (N8), Nessieria species (N9), Corynebacterium species (N10), Proteus species (N11), Bacillus species (N12) and Klebsiella species (N13). Enterobacter species was identified as the most frequently isolated organism. These isolates were further screened against some known human pathogens; Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella pneumoniae and Salmonella species. The result showed that one of the Enterobacter species (N1) has activity on all the pathogens, the other Enterobacter species (N2) has activity against four except Klebsiella pneumoniae and the last Enterobacter species (N3) has activity also against four pathogens except Salmonella species while Pseudomonas species have activity against three of the pathogens except Klebsiella pneumonia and Escherichia coli. Lastly, Staphylococcus epidermidis has activity on two pathogens and no activity on Pseudomonas aeruginosa, Klebsiella pneumoniae and Escherichia coli. This study showed that some soil microorganisms could be an interesting source of antimicrobial substances against some human pathogens. Pharmaceutical industries can explore this ability during antimicrobial production and synthesis.
Keywords: Antibiotic; Antimicrobial; Screening; Isolation; Abattoir